Pool size structure indicates developmental stages of boreal fens - White, Marianne; Payette, Serge (Botany, 2016)
Several boreal fens belong to the patterned fen category, which is composed of two compartments, the pool (or hollow), and the string (or hummock) compartments. Both compartments are distributed perpendicular to the mire slope and drainage flow. The surface of patterned fens is repeatedly invaded by water, which is known to affect the original pool–string pattern through the creation and enlargement of pools, a process caused by the action of aqualysis. Aqualysis refers to the destruction of the vegetation cover by flooding of low-elevated strings or lawns causing the formation and enlargement of pools. It is argued here that the nature and composition of the pool structure (number and size) reveal the state of development of patterned fens of the boreal environment. Quantitative and spatial data for pool size structure in 24 fens of northern Quebec, including 4881 pools, were used for the assessment of patterned fen development. Among the main factors influencing patterned fen development, area and slope contribute to the construction of the peatland surface. Also, watershed area, alternating strings and hollows, and peat thickness all facilitate pool creation and expansion. The construction of the pool structure of most fens has been a long process of ecosystem building. This probably explains why most sloping fens, i.e, moderate- and steep-sloping fens, are today at an equilibrium stage characterized by the coexistence of pools of all sizes with the smallest pools being the most numerous. In contrast, most low-sloping fens have developed toward a lacustrine stage with a bimodal distribution of small and very large pools. Boreal patterned fens of all developmental stages will be subject to increased pool size and number in the near future if more humid climatic conditions prevail.